Microbial inulinase promotes fructan hydrolysis under simulated gastric conditions - Guice, Justin L.; Hollins, Morgan D.; Farmar, James G.; Tinker, Kelly M.; Garvey, Sean M. (Frontiers in Nutrition, 2023)
Fermentable oligo-, di-, monosaccharides and polyols (FODMAPs) have emerged as key contributors to digestive discomfort and intolerance to certain vegetables, fruits, and plant-based foods. Although strategies exist to minimize FODMAP consumption and exposure, exogenous enzyme supplementation targeting the fructan-type FODMAPs has been underexploited. The objective of this study was to test the hydrolytic efficacy of a food-grade, non-genetically engineered microbial inulinase preparation toward inulin-type fructans in the INFOGEST in vitro static simulation of gastrointestinal (GI) digestion. Purified inulin was shown to undergo acid-mediated hydrolysis at high gastric acidity as well as predominantly inulinase-mediated hydrolysis at lower gastric acidity. Inulinase dose-response simulations of inulin, garlic, and high-fructan meal digestion in the gastric phase suggest that as little as 50 inulinase units (INU) and up to 800 INU per serving promote fructan hydrolysis better than the control simulations without inulinase. Liquid chromatography-mass spectrometry (LC-MS) profiling of fructo-oligosaccharides (FOS) in the gastric digestas following inulinase treatment confirms the fructolytic activity of inulinase under simulated digestive conditions. Altogether, these in vitro digestion data support the use of microbial inulinase as an exogenous enzyme supplement for reducing dietary fructan-type FODMAP exposure.